Profiling of Protein Degraders in Cultures of Human Gut Microbiota - Amaretti, Alberto; Gozzoli, Caterina; Simone, Marta; Raimondi, Stefano; Righini, Lucia; Pérez-Brocal, Vicente; García-López, Rodrigo; Moya, Andrés; Rossi, Maddalena (Frontiers in Microbiology, 2019)
Unabsorbed proteins reach the colon and are fermented by the microbiota, yielding a variety of harmful metabolites. In the present study, a 16S rRNA gene survey identified the bacterial taxa flourishing in 11 batch fermentations with proteins and peptones as sole fermentable substrates, inoculated with the feces of 6 healthy adults. Organic acids, ammonia, and indole accumulated in all the cultures, resulting from protein breakdown and fermentation. Analysis of differential abundances among time-points pointed out Enterobacteriaceae, Burkholderiaceae, and Desulfovibrionaceae (including Esherichia-Shigella, Sutterella, Parasutterella, and Bilophila) among the bacteria that responded most positively, especially in the cultures with low inoculation load. Lachnospiraceae and Ruminococcaceae also encompassed many taxa that significantly expanded, mainly in cultures inoculated with high inoculation load, and showed the strongest correlation with the production of ammonium, indole, and p-cresol. Anaerotruncus, Dorea, Oscillibacter, Eubacterium oxidoreducens, Lachnoclostridium, Paeniclostridium, Rombutsia were among them. Other Firmicutes (e.g. Roseburia, Ruminococcus, Lachnospira, Dialister, Erysipelotrichaceae, Streptococcaceae) and many Bacteroidetes (e.g. Barnesiellaceae, Prevotellaceae, Rickenelliaceae) decreased. Sequences attributed to Bacteroides, unresolved at the level of species, presented opposite contributions, resulting in no significant changes of the genus. This study shed light on the multitude of bacterial taxa putatively participating to protein catabolism in the colon. Protein fermentation was confirmed as unfavorable for health, for both the production of toxic metabolites and for the bloom of opportunistic pathogens and pro-inflammatory bacteria.